Adsorption of copper ions onto activated carbon from capsicum straw. Issue 1 (2nd January 2016) - Shou, Jianxin; Qiu, Muqing
Abstract: Activated carbon was obtained from capsicum straw by chemical activation using KOH as an activator. Then, it was used as an adsorbent for the removal of copper ions from aqueous solution. The effects of various parameters such as contact time, initial copper ion concentration, and temperature on copper ions adsorption by activated carbon were investigated. The experimental data were analyzed by the Langmuir and Freundlich models of adsorption. Kinetic adsorption data were analyzed by the pseudo-first-order kinetic model, the pseudo-second-order model, and the intraparticle diffusion model, respectively. The thermodynamics parameters were also calculated. The activated carbon was found to be both effective and economical.